Implementasi Budaya Risiko dalam Pengelolaan Perbankan Syariah di Indonesia - Pranoto Effendi (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Islamic banking requires risk management with a better approach. So far, regulatory and supervisory approaches have been prioritized in managing and mitigating the risks faced. It is time for emphasis to be given to a cultural approach that further motivates banks to mature in risk management. This article aims to discuss the importance of risk culture aspects in managing risk management in Islamic banks. Case studies were conducted on two banks, namely Bank Muamalat Indonesia and Bank Mega Syariah. The analysis was carried out qualitatively using secondary data sourced from annual reports. The findings show that the concept of risk culture has been implemented in the two Islamic banks but needs to be further improved both in terms of conceptual aspects and also in terms of practice.